Cumhuriyet döneminde Heybeliada (1923’ten günümüze) - Güngör, Esra (My University, 2013)
Çalışmamızda Cumhuriyet döneminde Heybeliada tarihi ele alınmıştır. Cumhuriyetin kuruluşundan itibaren Heybeliada ile ilgili kaynaklar incelenmiş ve bu kaynaklara göre adanın tarihi çıkarılmıştır. Adanın siyasi, sosyal, kültürel tarihi hem birincil hem de ikincil kaynaklar incelenerek yazılmıştır. Ada’da azınlıkların veya Türklerin nüfus yoğunluğu siyasi durumların belirlenmesinde etkin bir rol oynamıştır. Yine aynı şekilde nüfusun kültürel alanı ve kurumları da nasıl etkilediği gözler önüne serilmiştir. Heybeliada Sanatoryumu ile birlikte adanın günümüzdeki sağlık koşulları verilmiştir. Bunlardan başka spora ve adaya gelip giden, yaşayan önemli şahsiyetlere değinilmiştir.

Our study deals with the history of the Heybeliada in the republic period. Sources that related to the Heybeliada-even the sources that belong to the early republican era- was examined, and according to these sources the island’s history is written. Island’s political, social and cultural history was written by examining both primary and secondary sources. Both minorites and the Turks population played an important role to determine their political situation. Also, the effects of the population to the cultural field and the institutions was also examined in this study. Along with the Heybeliada Sanatorium the medical condition of the island was also studied in this work. Also, sport activities within the island and the famous people that visited or stayed the island was examined.
Keywords: Adalar (İstanbul, Türkiye); Heybeliada (İstanbul, Türkiye); Tarih; Türkiye